Peranan Quality Control Dalam Modern Packaging - Edi Witojo Kaswadi (Balai Besar Kimia dan Kemasan, 1977)
The characteristics of modern packaging are standard of volume, size or package weight and contents, filling process and design of package.In the field of modern packaging, the role of quality control are in the optimal total standard packaging, size, in the filling process and labelling, and in the determination of optimal packaging size which can be handled or transported efficiently.